2013
DOI: 10.1371/journal.pone.0056910
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Model of Tumor Cell Extravasation

Abstract: Tumor cells that disseminate from the primary tumor and survive the vascular system can eventually extravasate across the endothelium to metastasize at a secondary site. In this study, we developed a microfluidic system to mimic tumor cell extravasation where cancer cells can transmigrate across an endothelial monolayer into a hydrogel that models the extracellular space. The experimental protocol is optimized to ensure the formation of an intact endothelium prior to the introduction of tumor cells and also to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

14
210
0
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 214 publications
(226 citation statements)
references
References 45 publications
14
210
0
2
Order By: Relevance
“…cancer cell migration, adhesion (23), and extravasation (24,25). Recently, our group presented a microfluidic model to investigate the specificity of breast cancer metastasis to bone, providing quantitative data on cancer cell extravasation rate and reproducing the effects of the CXCL5-CXCR2 interaction between bone cells and metastatic breast cancer cells observed in vivo (26).…”
Section: Significancementioning
confidence: 99%
“…cancer cell migration, adhesion (23), and extravasation (24,25). Recently, our group presented a microfluidic model to investigate the specificity of breast cancer metastasis to bone, providing quantitative data on cancer cell extravasation rate and reproducing the effects of the CXCL5-CXCR2 interaction between bone cells and metastatic breast cancer cells observed in vivo (26).…”
Section: Significancementioning
confidence: 99%
“…Recently, several studies using microfluidic platform have been reported that recreate the 3D context of each aspect of the TME and metastasis in vitro. [10][11][12][13] However, to our knowledge, no versatile in vitro experimental model that reconstitutes direct interplay between constituents of the TME during tumorigenesis has yet been reported. Here we describe a biomimetic TME model to mimic the complex inter actions of the tumor, stromal, and endothe lial cells, all of which are essential components of the TME that hinder the effective treatment of cancers.…”
mentioning
confidence: 99%
“…The process consists of TC transport via the blood circulation, survival of the shear stress, arrest and attachment to a vessel wall and trans-endothelial invasion across the vessel wall and into the secondary metastatic site [54]. Two possible modes have been proposed…”
mentioning
confidence: 99%
“…The first, as described in the famous hypothesis by Paget, proposes that tumours of different organs show unique patterns of metastatic colonisation (seed) to other specific organ microenvironments (soil) through site-selective adhesion [45,54,55]. The second mode of extravasation hypothesises that due to the slightly larger size of TCs and their ability to aggregate with platelets, they become trapped in small vessels and capillary beds [56,57].…”
mentioning
confidence: 99%
See 1 more Smart Citation